The Snapshots of A. Thomas Nelson: A Case Study in the Preservation of Early 20th-century Vernacular Albums. Issue 2 (June 2018) - Becker, Stephanie
Throughout the early 20th century, A. Thomas Nelson took snapshots while traveling the United States and Canada. His wife, Catherine Nelson, made a selection of these and placed them within eight photographic albums, later acquired by the George Eastman Museum in Rochester, New York. Using one of these, "Snapshots from Travels in the United States and Canada (1904–1940), " as a case study, this article explores preservation practices for early 20th-century vernacular albums. While such albums are a valuable part of any collection, they present many complex preservation challenges due to the variety of materials contained within a single object. Critical questions about cataloging, digitizing, and rehousing methods guide decisions on how to stabilize the album's fragile condition and allow for access. This case study offers insight for collection managers and archivists who find themselves caring for similar snapshot albums.